Monitoring of dopamine and its metabolites in brain microdialysates: method combining freeze-drying with liquid chromatography-tandem mass spectrometry - Syslová, Kamila; Rambousek, Lukáš; Kuzma, Marek; Najmanová, Věra; Bubeníková-Valešová, Věra; Slamberová, Romana; Kačer, Petr (Journal of chromatography. A, Including electrophoresis and other separation methods, 2011)
A sensitive assay method was developed for a parallel, rapid and precise determination of dopamine and its metabolites, homovanillic acid, 3-methoxytyramine and 3,4-dihydroxyphenylacetic acid, from brain microdialysates. The method consisted of a pre-treatment step, freeze-drying (lyophilization), to concentrate dopamine and its metabolites from the microdialysates, and a detection step using liquid chromatography combined with electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS). In particular, the reaction monitoring mode was selected for its extremely high degree of selectivity and the stable-isotope-dilution assay for its high precision of quantification. The developed method was characterized by the following parameters: the precision of the developed method was determined as ≥88.6% for dopamine, ≥89.9% for homovanillic acid, ≥86.1% for 3-methoxytyramine and ≥88.1% for 3,4-dihydroxyphenylacetic acid; the mean accuracy was determined as ≥88.2% for dopamine, ≥88.3% for homovanillic acid, ≥85.9% for 3-methoxytyramine and ≥88.6% for 3,4-dihydroxyphenylacetic acid. The developed method was compared to (1) other combinations of pre-treatment methods (solid phase extraction and nitrogen stripping) with LC-MS and (2) another detection method, liquid chromatography, with electrochemical detection. The novel developed method using combination of lyophilization with LC-ESI-MS/MS was tested on real samples obtained from the nucleus accumbens of rat pups after an acute methamphetamine administration. It was proven that the developed assay could be applied to both a simultaneous analysis of all four substrates (dopamine, homovanillic acid, 3-methoxytyramine and 3,4-dihydroxyphenylacetic acid) in microdialysis samples acquired from the rat brain and the monitoring of their slight concentration changes on a picogram level over time following methamphetamine stimulus.
Keywords: methamfetamin; stabilita léku; Animals; Methamphetamine; Female; Rats, Wistar; kyselina 3,4-dihydroxyfenyloctová; Linear Models; ženské pohlaví; Tandem Mass Spectrometry; kyselina homovanilová; Reproducibility of Results; Nucleus Accumbens; Dopamine; Sensitivity and Specificity; Chromatography, Liquid; Drug Stability; Microdialysis; senzitivita a specificita; lineární modely; mikrodialýza; Homovanillic Acid; reprodukovatelnost výsledků; tandemová hmotnostní spektrometrie; nucleus accumbens; krysa rodu Rattus; dopamin; Freeze Drying; zvířata; lyofilizace; Rats; chromatografie kapalinová; 3,4-Dihydroxyphenylacetic Acid; potkani Wistar